2010
DOI: 10.3109/00365599.2010.521186
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radical and partial nephrectomy in terms of renal function: A retrospective cohort study

Abstract: After surgical treatment of renal masses, patients are at risk for development of chronic renal failure. A decrease in GFR was detected in both partial and radical nephrectomy, the latter associated with increased risk, especially in hypertensive patients. Routine praxis of radical nephrectomy should be overviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…This is consistent with the results of previous studies [9,15,16]. RN has previously been found to be associated with a greater risk of de novo chronic renal failure than PN is [1,3,8,9,10,11], and our results similarly demonstrated that this risk was significantly greater in the RN group.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is consistent with the results of previous studies [9,15,16]. RN has previously been found to be associated with a greater risk of de novo chronic renal failure than PN is [1,3,8,9,10,11], and our results similarly demonstrated that this risk was significantly greater in the RN group.…”
Section: Discussionsupporting
confidence: 94%
“…eGFR can be determined at a lower cost and more conveniently and is suitable for clinical use. It has therefore been used in several studies assessing renal function after operations for RCC [8,9]. The Modification of Diet in Renal Disease (MDRD) Study equation is most commonly used to estimate GFR [13], but this equation is less accurate for Asians, with greater bias at eGFR of <60 ml/min/1.73 m 2 [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of renal function is decreased following PN compared with that following radical nephrectomy (RN), and oncological management is reportedly equivalent between PN and RN (1,4). Although patients following RN are not likely to exhibit severe renal dysfunction requiring hemodialysis (5,6), 65% of patients develop grade 3 chronic kidney disease, defined as an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m 3 , 3 years after nephrectomy (7) and the decrease in eGFR may lead to an increased risk of cardiovascular-related death in the future (8,9). Therefore, the preservation of renal function as well as cancer management should be considered in the treatment of RCC.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, hypertension was an independent predictor of CKD upstage. Suer et al (25) studied the longterm impact of hypertension and diabetes mellitus on GFR in the long term in 488 patients submitted to nephrectomy and noted that hypertension was associated with new onset of chronic renal failure only in the radical nephrectomy group (HR 1.39, 95% CI 1.02 -1.89).…”
Section: Discussionmentioning
confidence: 99%